Biological Control for Insect Management in Strawberries - Silvia I. Rondon; Daniel J. Cantliffe; James F. Price (EDIS, 2003)
The strawberry, Fragaria ananassa Duch., is an intensively cultivated high value crop that requires inputs of chemicals, including insecticides and miticides. Through early identification of arthropod problems, and targeted releases of reared beneficial insects and mites, it may be feasible to minimize the requirements for pesticides on strawberry. This document is HS923, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: June 2003.